PENGARUH PENERAPAN MODEL LEARNING CYCLE DISERTAI PERTANYAAN DITEMPEL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMA NEGERI 15 PADANG TAHUN PELAJARAN 2013/2014 - Zahara, Rina; K, Delsi.; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
The research of this background is based on the students understanding of mathematical concepts have minimum level, in pre-teaching,Â the teacher do not generate interest of the students and do not give motivation to the students, students tend to be passive and reluctant to ask. The aims of This study is to determine whether students understanding of mathematical concepts by applying the Learning Cycle models are better than student understanding of mathematical concepts by applying conventional learning in class XI students of SMA Negeri 15 Padang. Type of this research is experimental research, the researcher choose the sample of research using Random Subjects . The population of this study was four class of XI IPA students of SMA Negeri 15 Padang academic year 2013/2014. The sample was IPA2 class as the experimental classÂ and class XI IPA1 as the control class. The Instruments that used in this research is a test of understanding mathematical concepts. Based on the analysis of the data found that the two classes are normally and homogeneous samples at Î± = 0.05 and the results obtained from testing the hypothesis P-value = 0.007 means less than Î± = 0.05, so it means that the hypothesis in this study is received . It can be concluded that the students understanding of mathematical concepts that apply the Learning Cycle Model with taped questions better than students understanding of mathematical concepts by applying conventional learning in class XI student of SMA Negeri 15 Padang.